A Guide to Magnetic Tweezers and Their Applications - Sarkar, Rupa; Rybenkov, Valentin V. (Frontiers in physics, 2016)
Magnetic force spectroscopy is a rapidly developing single molecule technique that found numerous applications at the interface of physics and biology. Since the invention of the first magnetic tweezers, a number of modifications were incorporated into the approach that helped relieve the limitations of the original design and amplified its strengths. Inventive molecular biology solutions further advanced the technique by expanding its possible applications. In its present form, the method can be applied to single molecules and live cells without resorting to intense sample irradiation, can be easily multiplexed, accommodates multiple DNAs, displays impressive resolution, and allows a remarkable ease in stretching and twisting macromolecules. In this review, we describe the architecture of magnetic tweezers, key requirements to the experimental design and analysis of data, and outline several applications of the method that illustrate its versatility.